GANGGUAN EMOSI DAN PERILAKU PADA ANAK YANG MENGALAMI PENYAKIT KRONIS - Julinar Julinar (Jurnal Sains Riset, 2021)
Chronic disease is a condition that affects daily functioning for three months or more and occurs within one year. Chronic illness generally refers to a physical, emotional, or developmental condition that affects a child for a long period. Emotional control in children is a tendency to hide and suppress negative emotions such as anger, depression, or anxiety. This study uses a quantitative descriptive method with a cross-sectional approach. Data collection methods used were PSC-17 questionnaires and interviews. As for the sample of this study 20 respondents. Sampling in this study using the Total Sampling technique. The conclusion of the study found that the types of leukemia, thalassemia, and chronic kidney disease as a whole did not experience behavioral disorders and the assessment showed that there was a tendency for normal respondents who did not experience interference based on the total score but experienced problems in one of the behavioral disorders such as aspects of Internalization, Attention, Externalization, and Total score.Keywords: Chronic Disease, Emotional Control, Behavioral Tendency